Geraniol and Citral as potential therapeutic agents targeting the HSP90 activity: An in silico and experimental approach. (March 2022) - Gaonkar, Roopa; Singh, Jitender; Chauhan, Arushi; Avti, Pramod K.; Hegde, Gurumurthy
Abstract: Lemongrass essential oil has antifungal and anti-cancerous properties. Heat-shock protein (HSP90), an ATP-dependent molecular chaperone found in eukaryotes, is involved in protein folding, stability, and disease, making it a promising research topic. Both in silico and in vitro approaches were used to provide a clear insight into the HSP90-ATPase 3D structures, activity, and their interaction with the essential oil constituents among various species such as fungi (S. cerevisiae ), parasites ( P. falciparum), and humans. For in silico studies, sequence alignment, docking (AutoDock), and absorption, distribution, metabolism, and excretion (ADME) properties were evaluated to obtain hit compounds specifically against each HSP90-ATPase. The hit compounds obtained were evaluated for their efficacy in the in vitro studies of S. cerevisiae . In vitro studies were carried out targeting HSP90-ATPases via lemongrass essential oil components individually and in combination as a function of concentration and various salt concentrations. Results suggest that sequence alignment exists of over 75% among these three species. The best docking score was possessed by Geraniol and its constituent (geldanamycin ≥ −4.93 kcal/mol) (a known antifungal and antitumor against HSP90) in all the above species . Lemongrass oil and the combination of Geraniol and Citral at concentrations of 80 μg/mL showed the maximum inhibition of ATPase and HSP90-ATPase activity compared to their individual treatment. Therefore, both in silico and in vitro studies provide clear evidence of specific inhibitory action of lemongrass oil, Geraniol, and Citral against the ATPase and HSP90–ATPase activities and might show potential as antifungal and antitumor drugs. Graphical abstract: Structure-activity relationship of lemongrass oil constituents showing potential therapeutic efficacy against HSP90-ATPase activity through in silico and in vitro investigations. Image 1 Highlights: Good sequence alignment - H. sapiens, P. falciparum & S. cerevisiae HSP90 target. Geraniol, geranyl acetate and Citral as HSP90 hit compound(s) – Autodock screening. Good pharmacokinetic properties of the compounds. HSP90-ATPase Inhibition, anti-fungal efficacy by EO - In vitro studies. Geraniol, geranyl acetate & Citral as potential anti-fungal & anti-cancer agents.